THE WASHBACK EFFECT OF SCHOOL-BASED ORAL EVALUATION PERFORMANCE AND ITS CAUSAL RELATIONSHIP WITH FEAR OF NEGATIVE EVALUATION - Rosnah Mohd Sham; Mohd Nazri Latiff Azmi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
This paper presents part of a study that investigates the washback effect of a School-Based Oral Evaluation (SBOE) performance from the teachers’ perceptions.  It also investigates the causal relationship between students who have passed in the school-based oral evaluation (SBOE) with fear of negative evaluation. The participants are 302 of form four students and four English teachers from the Putrajaya Federal Territory government secondary schools in Malaysia. It is a mixed-method study in which data were collected in sequential, analysed separately, and then explained. The quantitative data were collected by using FLCAS, the School-Based Oral Evaluation (SBOE) results and the qualitative data were collected from the semi-structured interviews with the English teachers and guidelines on SBOE from the Ministry of Education Malaysia. The quantitative method used descriptive statistical analysis, whereas the qualitative method used content analysis.  Students’ result in the mid-term examination 2017 had shown that they scored high marks in the SBOE.  The quantitative results revealed that the students experienced low mean level of fear of negative evaluation.  The teachers reported that students had shown positive attitude during the SBOE and English class interaction.  They were focused, confident, responsive and not panic.  There is a positive washback effect of SBOE on the students’ result. High results in SBOE affected the mean level of fear of negative evaluation. The partial eta-squared showed the value of 0.106 which is considered high.  This study suggests two broad future tasks.  The first task involves the development of national curriculum in English language which dependence upon oral English language.  The second task focuses on the development of English language training and skills for the English teachers.Keywords: washback effect, School-Based Oral Evaluation performance, causal relationship, fear of negative evaluation